![x + y = 2a {}^{2} \\ x(a - b + \frac{ab}{a - b}) = y(a + b - \frac{ab}{a + b}) x + y = 2a {}^{2} \\ x(a - b + \frac{ab}{a - b}) = y(a + b - \frac{ab}{a + b})](https://tex.z-dn.net/?f=x+%2B+y+%3D+2a+%7B%7D%5E%7B2%7D++%5C%5C+x%28a+-+b+%2B++%5Cfrac%7Bab%7D%7Ba+-+b%7D%29+%3D+y%28a+%2B+b+-++%5Cfrac%7Bab%7D%7Ba+%2B+b%7D%29+)
Answers
Answered by
5
Given pair of linear equations are
and
can be rewritten as
Now, we have 2 equation in simplified form as
and
Now, using cross multiplication method, we have
So, now
Taking first and third member, we have
Taking second and third member, we have .
Consider, equation (1),
On substituting the values of x and y, we have
Hence, Verified
Similar questions